Results of intravenous thrombolysis within 4.5 to 6 hours and updated results within 3 to 4.5 hours of onset of acute ischemic stroke recorded in the Safe Implementation of Treatment in Stroke International Stroke Thrombolysis Register (SITS-ISTR): an observational study - Ahmed, Niaz; Kellert, Lars; Lees, Kennedy R.; Mikulik, Robert; Tatlisumak, Turgut; Toni, Danilo (JAMA neurology, 2013)
IMPORTANCE: Pooled analysis of randomized controlled trials of intravenous thrombolysis shows no statistically significant benefit beyond 4.5 hours, with the possible advantage perhaps offset by risk. - OBJECTIVE: To compare the outcomes of patients who were treated within 4.5 to 6 hours or within 3 to 4.5 hours of the onset of an ischemic stroke with the outcomes of patients who were treated within 3 hours in the SITS-ISTR. - DESIGN: An observational study based on SITS-ISTR data during the period from 2002 to 2011. - SETTING: Acute and emergency care. - PARTICIPANTS: Of 29 618 patients with acute ischemic stroke, 283 (1.0%) were treated within 4.5 to 6 hours of onset, 4056 (13.7%) were within 3 to 4.5 hours of onset, and 25 279 (85.4%) were treated within 3 hours of onset, in compliance with other European Union approval criteria. - EXPOSURE: Intravenous thrombolysis with alteplase. - MAIN OUTCOMES AND MEASURES: Functional independence (modified Rankin Scale score of 0-2) and mortality at 3 months and symptomatic intracerebral hemorrhage (SICH). P values are based on comparisons between patients treated within 4.5 to 6 hours or within 3 to 4.5 hours of onset against patients treated within 3 hours of onset. - RESULTS: Results are presented as within 4.5 to 6 hour vs within 3 to 4.5 hours vs within 3 hours. Median time from stroke onset to treatment was 295 vs 210 minutes vs 138 minutes (P < .01), median age was 65 vs 67 vs 68 years (P < .01), and median baseline National Institutes of Health Stroke Scale score was 9 vs 9 vs 12 (P < .01). Rate of functional independence was 61.3% (P = .40) vs 62.7% (P < .01) vs 58.4%; mortality rate was 11.8% (P = .99) vs 11.1% (P = .21) vs 11.8%; and rate of SICH was 2.6% (P = .17) vs 1.8% (P = .27) vs 1.5%. Multivariate analysis detected no significant difference in SICH (P > .05), mortality (P > .05), or independence (P > .05). Time from stroke onset to treatment as a continuous variable was significantly associated with higher rates of SICH and poor 3-month outcome after adjustment for age and National Institutes of Health Stroke Scale score. - CONCLUSIONS AND RELEVANCE: The treatment remains safe and effective for patients treated within 3 to 4.5 hours compared with patients treated within 3 hours. Our selected group of patients treated within 4.5 to 6 hours of stroke onset did not have worse outcomes than patients treated within 3 hours. An inevitable limitation of our observational study is the possible nonequivalence of the cohorts, particularly the 4.5- to 6-hour cohort relative to the other 2 cohorts.